Development of a Preoperative Adult Spinal Deformity Comorbidity Score That Correlates With Common Quality and Value Metrics: Length of Stay, Major Complications, and Patient-Reported Outcomes - Sciubba, Daniel (Global Spine J, 2019)
STUDY DESIGN: Retrospective review of a multicenter prospective registry. OBJECTIVES: Our goal was to develop a method to risk-stratify adult spinal deformity (ASD) patients on the basis of their accumulated health deficits. We developed a novel comorbidity score (CS) specific to patients with ASD based on their preoperative health state and investigated whether it was associated with major complications, length of hospital stay (LOS), and self-reported outcomes after ASD surgery. METHODS: We identified 273 operatively treated ASD patients with 2-year follow-up. We assessed associations between major complications and age, comorbidities, Charlson Comorbidity Index score, and Oswestry Disability Index score. Significant factors were used to construct the ASD-CS. Associations of ASD-CS with major complications, LOS, and patient-reported outcomes were analyzed. RESULTS: Major complications increased significantly with ASD-CS (P < .01). Compared with patients with ASD-CS of 0, the odds of major complications were 2.8-fold higher (P = .068) in patients with ASD-CS of 1 through 3; 4.5-fold higher (P < .01) in patients with ASD-CS of 4 through 6; and 7.5-fold higher (P < .01) in patients with ASD-CS of 7 or 8. Patients with ASD-CS of 7 or 8 had the longest mean LOS (10.7 days) and worst mean Scoliosis Research Society–22r total score at baseline; however, they experienced the greatest mean improvement (0.98 points) over 2 years. CONCLUSIONS: The ASD-CS is significantly associated with major complications, LOS, and patient-reported outcomes in operatively treated ASD patients.